1983
DOI: 10.1080/00288330.1983.9515987
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and distribution of pathogenic free‐living amoebae in thermal areas of the North Island of New Zealand

Abstract: A sample survey of 9 thermal pools or streams in 3 Health Districts of the North Island of New Zealand was made over a 15-month period to determine the presence or absence of pathogenic free-living amoeba (PFLA) of the genera Naegleria and Acanthamoeba. Concurrent chemical, physical, and bacteriological analyses of the pools were made. Naegleria and Acanthamoeba were isolated in the Rotorua and Hamilton Health Districts but not in the Gisborne Health District. Most PFLA were isolated from water with a high col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 39 publications
(39 reference statements)
0
24
0
Order By: Relevance
“…fowleri has been isolated from numerous water sources, especially industrial water with artificially elevated temperatures, swimming pools, thermal springs, and domestic water supplies (Brown et al 1983;Cerva et al 1982;DeJonckheere and Van de Voorde 1977;Fliermans et al 1979;Kasprzak et al 1982;Tyndall et al 1989;Wellings et al 1977). Improved methods of detection are needed in order to prevent recreational use of contaminated water.…”
Section: Discussionmentioning
confidence: 97%
“…fowleri has been isolated from numerous water sources, especially industrial water with artificially elevated temperatures, swimming pools, thermal springs, and domestic water supplies (Brown et al 1983;Cerva et al 1982;DeJonckheere and Van de Voorde 1977;Fliermans et al 1979;Kasprzak et al 1982;Tyndall et al 1989;Wellings et al 1977). Improved methods of detection are needed in order to prevent recreational use of contaminated water.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, the flow and circulation pattern of water in Lake Anna could contribute to the low level of N. fowleri. Sykora et al (1983) and Brown et al (1983) reported that N. fowleri may occur more frequently in water that is contaminated by high concentrations of total coliform bacteria. In this context, water temperature could serve as a linked factor to increased incidence of N. fowleri since it promotes the growth of bacteria that serve as its food source.…”
Section: Discussionmentioning
confidence: 99%
“…Millions of people in Taiwan enjoy bathing in hot spring tubs (Hsu et al 2008). Naegleria and their intracellular parasites are able to tolerate high temperatures and survive in high water temperature environments; therefore, they can easily thrive in both natural and artificial hot water systems (Brown et al 1983;Rivera et al 1993). For that reason, it is important to rapidly detect Naegleria and its parasites in hot spring facilities where people swim and bathe.…”
Section: Introductionmentioning
confidence: 99%